Structure and Magnetic Property Control of Copper Hydroxide Acetate by Non‐Classical Crystallization. Issue 9 (16th December 2016) - Song, RuiQi; Krasia‐Christoforou, Theodora; Debus, Christian; Cölfen, Helmut
Abstract : Copper hydroxide acetate (CHA), one layered hydroxide compound with tunable magnetism, attracts great interest because of its potential applications in memory devices. However, ferromagnetism for CHA is only demonstrated by means of GPa pressure. Herein, a new method is reported, involving the combination of different crystallization pathways to control crystallization of amorphous CHA toward the formation of CHA/polymer composites with tunable magnetic properties and even a tunability that can be tested at room temperature. By using poly[(ethylene glycol)6 methyl ether methacrylate]‐ block ‐poly[2‐(acetoacetoxy) ethyl methacrylate] (PEGMA‐ b ‐PAEMA) diblock copolymers as additives in combination with a post‐treatment process by ultracentrifugation, it is demonstrated that CHA and PEGMA‐ b ‐PAEMA form composites exhibiting different magnetic properties, depending on CHA in‐plane nanostructures. Analytical characterization reveals that crystallization of CHA is induced by ultracentrifugation, during which CHA nanostructures can be well controlled by changing the degrees of polymerization of the PEGMA and PAEMA blocks and their block length ratios. These findings not only present the first example of using crystallization from polymer stabilized amorphous precursors toward the generation of magnetic nanomaterials with tunable magnetism but also pave the way for the future design of functional composite materials. Abstract : An approach to prepare copper hydroxide acetate (CHA)/polymer composite materials with tunable magnetic properties via crystallization is developed. Through using block copolymer additives and ultracentrifugation synergistically, crystallization of CHA can be controlled. Different from all previously reported CHA‐based materials, the resulting composites exhibit magnetic property tunability, which is dependent on CHA nanostructures.